TELOLET HORN SETTINGS BASED ON LEGISLATION IN INDONESIA - Yulia Hesti; Suta Ramadan; Aprinisa Aprinisa; Pika Sari (Law Faculty of Universitas Bandar Lampung, 2023)
The use of telolet horns is currently increasingly popular in Indonesia. Telolet horn is a type of horn that produces a unique and distinctive sound. The phenomenon of